2022
DOI: 10.54910/sabrao2022.54.5.17
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Tomato Germplasm for Salinity Tolerance at the Seedling Stage

Abstract: Salinity consists of critical abiotic stress adversely affecting tomato growth and development. Given the increase in saline areas, breeders endeavor to develop crops that can tolerate salinity. It indicates the importance of genotypes that can grow in salt-affected soil to cope with the problem. This study focused on identifying salt-tolerant and salt-sensitive genotypes using Principal Component Analysis (PCA). This study used a two-factor factorial under a complete randomized design, with three replications… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 18 publications
0
0
0
Order By: Relevance
“…Food preservatives are beneficial in preserving the nutrients of many food materials to satisfy the demands of the consumers through an improvement in texture, colour, taste, etc. (Kumar et al, 2015;Udah, 2021). Ideally, preservatives addition in foods helps to maintain several different qualities.…”
Section: Preservativesmentioning
confidence: 99%
“…Food preservatives are beneficial in preserving the nutrients of many food materials to satisfy the demands of the consumers through an improvement in texture, colour, taste, etc. (Kumar et al, 2015;Udah, 2021). Ideally, preservatives addition in foods helps to maintain several different qualities.…”
Section: Preservativesmentioning
confidence: 99%
“…Integral to the reliability of these evaluations is the construction of the evaluation index system, which significantly impacts the results' accuracy and stability [14,36]. Although prior studies have identified various early-stage traits of tomato as potential indicators of salt tolerance [12,20], the indiscriminate integration of these traits into evaluation systems can compromise the assessment's precision and stability [37]. To this end, this study systematically optimized the comprehensive evaluation process, developing a protocol that enhanced the assessment's stability and accuracy when applied to tomato germplasm salt tolerance.…”
Section: Salt Tolerance Analysis In Subpopulations Of the Initial Pop...mentioning
confidence: 99%
“…Additionally, tomatoes serve as a model plant for studying economically important traits, such as fruit development and flavor quality [18,19]. Nonetheless, as a moderately salt-sensitive crop, common tomato varieties typically exhibit limited salt tolerance [20,21]. Rising soil salinity levels have led to significant tomato yield losses, amounting to billions of dollars annually.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Magnesium is an essential element required as a cofactor for over 300 enzymatic reactions and is therefore necessary for the biochemical functioning of numerous metabolic processes [4]. Sodium is vital in the human body for regulating blood pressure, stimulating nerves and muscles; calcium has some very important life-supporting functions because it is a structural component of bones, teeth, and soft [5,6]. Phosphorus is a basic unit in DNA, and RNA and serves as an energy store in metabolic reactions of biological systems [7,8].…”
Section: Introductionmentioning
confidence: 99%